Recursos didácticos con materiales reciclables - Bobadilla Armijos, Verónica Lissette (2016)
The use of teaching resources with reusable materials from the environment does not exist in the school, for that reason a diagnosis on the knowledge of the importance and utilities that can provide the educational process making objects from recycled materials was performed. Through this research aims to regulate the selection, manufacture and use of various objects that can be considered as elementary teaching resources in some areas of knowledge, including natural science, mathematics and social sciences. The theoretical foundations are based on the constructivist theory, so it is a descriptive inquiry; design research and bibliographic record is framed in observation sheets and surveys are the techniques used; it teachers, parents and students applied and the results were tabulated properly and allowed more reliable criteria on the situation initially raised. The teacher has the responsibility to enrich their pedagogical practice with innovative and creative techniques for students to strengthen their knowledge, hence the importance of promoting free expression through creativity and artistic expression with materials that do not generate expenses. This research highlights the importance of the use and reuse of recyclable materials as a basic strategy within the learning and the beneficiaries are students who improve their knowledge creatively.